Analysis of Differences in Environmental Noise Levels and the Influence of Individual, Behavioral, and Environmental Factors on Hearing Threshold, Blood Pressure, and Habitual Sleep Efficiency - Renaningtyas Nityasani; Aditya Sukma Pawitra; Khuliyah Candraning Diyanah; Shamsul Bahari Shamsudin; Zainul Amiruddin Zakaria (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: Environmental noise from transportation, especially railways, is a form of sound pollution that affects health both auditorily and non-auditorily. Homemakers, who spend most of their time at home, are particularly vulnerable to noise exposure. This study aimed to analyze differences in hearing thresholds, blood pressure, and habitual sleep efficiency among homemakers residing in areas with varying noise levels, as well as contributing individual, behavioral, and environmental factors. Methods: This was an analytical observational study with a cross-sectional design involving 60 housewives—30 from a noise-exposed area (Ambengan Selatan Karya) and 30 from a quieter area (Rusunawa Wonorejo). Data were collected through noise measurements using a Sound Level Meter, audiometric tests, blood pressure measurements, and questionnaires inspired by the Pittsburgh Sleep Quality Index (PSQI). Statistical analyses included the Independent T-Test to analyze the differences in environmental noise level, the Mann-Whitney test to analyze the differences of each dependent variable, and the chi-squared test to analyze the influences. Results and Discussion: Significant differences were found in environmental noise levels (p=0.021), right ear hearing thresholds (p=0.039), blood pressure (p=0.007), and sleep efficiency (p=0.040). No significant difference was observed in left ear hearing thresholds. Factors influencing right ear hearing thresholds included age and earphone use, age influenced blood pressure, while physical barriers affected sleep efficiency. Conclusion: High exposure to environmental noise may increase the risk of hearing loss, hypertension, and sleep disturbances.